A Quantitative Metric for the Design of Selective Supercritical CO2 Extraction of Lithium from Geothermal Brine. Issue 15 (16th July 2019) - Ruttinger, Andrew W.; Pálsdóttir, Arna; Tester, Jefferson W.; Clancy, Paulette
Abstract: As demand grows for lithium, its recovery from geothermal brines provides an attractive alternative to slow mining. One promising extraction method uses crown ethers as extractants in supercritical carbon dioxide with cation exchangers to facilitate extraction from brine. Molecular dynamics modeling is used to understand the mechanism of binding between lithium (or sodium) and combinations of 14‐crown‐4 ethers and cation exchangers, and the predictive capability of computational modeling to test lithium selectivity is established for four combinations of crown ethers [methylene‐14‐crown‐4 (M14C4) and a fluorinated 14‐crown‐4 (F14C4)] and cation exchangers [di(2‐ethyl‐hexyl)phosphoric acid (HDEHP) and tetraethylammonium perfluoro‐1‐octanesulfonate (TPFOS)]. Binding free energies (given in kcal mol −1 ) of lithium and sodium, respectively, to crown ether–cation exchangers are 85 and 71 for M14C4–HDEHP, 90 and 71 for F14C4–HDEHP, 93 and 80 for M14C4–TPFOS, and 104 and 93 for F14C4–TPFOS. Good agreement is found between computational predictions and supercritical carbon dioxide extraction experiments at 60 °C and 250 bar. Binding free energy gives a suitable metric to describe extraction efficiency. Differences in the binding free energies of sodium and lithium to crown ethers determine the extraction selectivity. Fluorine groups are found to exert a positive influence to optimize extraction efficiency. Of the systems studied, F14C4 with TPFOS offers the most selective and efficient extraction system. Abstract : Crowning glory : Through a combined experimental and computational approach, binding free energy is found to be an accurate metric by which to quantify the selectivity and efficiency of lithium extraction by custom‐designed 14‐crown‐4 ethers in supercritical carbon dioxide by using a relationship derived from the chemical structure of the extractants.